Caribbean Report 08-02-1991 - Goffe, Leslie (anchor); Ransome, Debbie (correspondent); Alexis, Francis (interviewee); Croskill, Hugh (correspondent); Khan, Sharief (correspondent); Whitehorne, Pat (correspondent); Aming, Neville (interviewee); Awong, Max (interviewee); Hoyte, Desmond (interviewee); Herrenberg, Hendrik Frans (Henk) (interviewee); Adams, David (correspondent) (The British Broadcasting Corporation, 1991)
As Haiti’s new President, Rev. John Bertrand Aristide is sworn in as the country’s new President, David Adams reports on some of the decisions that the President plans to take. The President did not shy away from taking tough decisions as he dismissed some very senior military officials, most of them Generals, from the armed forces. His decisions are seen as an intelligent move and there are signs that the new Haiti will succeed although the elite class is not fully supportive of Rev. Aristide. Mr. Desmond Hoyte, Guyana’s President has shown support for the Surinamese military backed government and explains that no one can dictate his country’s foreign policy. Mr. Hoyte is the first Head of State to meet with the Suriname’s interim President, Johanne Kraag as Guyana did not join the other CARICOM countries in condemning the recent coup d’état in Suriname. Mr. Francis Alexis, Legal Affairs Minister of Grenada believes that the slow pace of integration in the Caribbean is due to historical circumstances since unity was not promoted in the Caribbean until the 2nd world war. He adds that there is need to understand the psyche of the people across the Caribbean region before any aspect of integration can succeed. He however believes that the region’s future lies in integration. If this does not happen he foresees that the bigger Caribbean islands may get into President Bush’s initiative on its own and there will be no option for the smaller Caribbean islands but to do the same. In Trinidad and Tobago, Debbie Ransome reports on how the country is getting prepared for its Carnival celebrations which takes place over the weekend. Despite the war in the Gulf, the country continues with its preparations although there is a decline in foreign visitors.
1. Headlines (00:00-01:02)
2. Haiti’s new President makes tough decisions to steer his new government takes up office (01:03-04:03)
3. Mr. Desmond Hoyte, President of Guyana argues that no one will dictate his country’s foreign policy (04:04-06:50)
4. Mr. Francis Alexis, Legal Affairs Minister of Grenada believes that the slow pace of integration in the Caribbean is due to historical circumstances (06:51-11:15)
Keywords: Haiti – Politics and Government.; Haiti – economic aspects.; Guyana – Politics and Government.; Suriname – Politics and Government.; Grenada – Politics and Government.; Caribbean area – economic conditions.; Carnival – Trinidad and Tobago.; Regional integration.; CARICOM.; Mas players -- Trinidad and Tobago.; Greatest show in the world, Trinidad and Tobago.; Aristide, Jean-Bertrand.; Kraag, Johannes Samuel Petrus (Johan)